Efficacy of mitoxantrone in neuromyelitis optica spectrum: clinical and neuroradiological study. Issue 5 (8th November 2012) - Cabre, Philippe; Olindo, Stephane; Marignier, Romain; Jeannin, Severine; Merle, Harold; Smadja, Didier
Abstract : Objective: To evaluate the efficacy of mitoxantrone (MTX) on clinical and neuroradiological parameters of patients who had a relapse of neuromyelitis optica spectrum (NMOS) within the 12 previous months. Methods: MTX (12 mg/m 2 ) combined with methylprednisolone 1 g as three monthly courses followed by three quarterly courses was administered during an observational multicentre open study including 51 consecutive patients (28 NMO, 23 limited forms of NMO) of the French Caribbean and Guyana. The main outcome measure was the reduction of the annualised relapse rate (ARR), and the secondary outcome measures were alteration of disability measured by expanded disability status scale (EDSS) score, the time to onset of the first relapse, and the progression of neuroradiological lesions at 1 year of treatment. Results: At 1 year of treatment, the ARR dropped from 1.82 to 0.37 (p<0.0001). The mean EDSS score improved by 1.3 points, going from 5.8 at baseline to 4.5 at 1 year (p<0.0001). The number of patients showing gadolinium (Gad)+ spinal cord lesions at baseline, that is, 46.9%, dropped to 10.6% (a 77.4% reduction; p=0.02). The median time to onset of the first relapse was 18 months. IgG-NMO seropositivity was a predictive factor of relapse (p=0.006). A case of acute myeloid leukaemia was observed after a mean time span of 4.8 years. Conclusions: In this observational NMO study, MTX decreased dramatically the frequency of relapses, which is directly related to progression of disability or even death in this disorder.